Smart radiation therapy biomaterials - Ngwa, Wilfred; Herskind, Carsten; Veldwijk, Marlon Romano; Hildenbrand, Georg Lars; Hausmann, Michael; Wenz, Frederik; Hesser, Jürgen (International journal of radiation oncology, biology, physics, 2017)
Radiation therapy (RT) is a crucial component of cancer care, used in the treatment of over 50% of cancer patients. Patients undergoing image guided RT or brachytherapy routinely have inert RT biomaterials implanted into their tumors. The single function of these RT biomaterials is to ensure geometric accuracy during treatment. Recent studies have proposed that the inert biomaterials could be upgraded to “smart” RT biomaterials, designed to do more than 1 function. Such smart biomaterials include next-generation fiducial markers, brachytherapy spacers, and balloon applicators, designed to respond to stimuli and perform additional desirable functions like controlled delivery of therapy-enhancing payloads directly into the tumor subvolume while minimizing normal tissue toxicities. More broadly, smart RT biomaterials may include functionalized nanoparticles that can be activated to boost RT efficacy. This work reviews the rationale for smart RT biomaterials, the state of the art in this emerging cross-disciplinary research area, challenges and opportunities for further research and development, and a purview of potential clinical applications. Applications covered include using smart RT biomaterials for boosting cancer therapy with minimal side effects, combining RT with immunotherapy or chemotherapy, reducing treatment time or health care costs, and other incipient applications.
Available online 1 November 2016
Gesehen am 25.06.2018